Faktor-Faktor yang Mempengaruhi Kepatuhan Konsumsi Pemberian Makanan Tambahan pada Ibu Hamil KEK - Ramah Hayu; Fanny Jesica; Dewi Fransisca; Melia Pebrina; Fenny Fernando (Poltekkes Kemenkes Padang, 2026)
Chronic Energy Deficiency (CED) among pregnant women significantly contributes to maternal and infant mortality. While the government provides Supplementary Feeding (PMT), the program's effectiveness is heavily dictated by consumption compliance. This study aimed to analyze factors influencing compliance among CED pregnant women in consuming PMT at Puskesmas Anak Air Padang in 2024. A descriptive analytic design with a cross-sectional approach was conducted on 31 respondents selected via simple random sampling. Data were collected through structured questionnaires and analyzed using the chi-square test (p < 0.05). Findings revealed that 61.3% of respondents were compliant in consuming PMT. Significant associations were found between compliance and maternal awareness (p=0.007), taste preferences (p=0.008), and family support (p=0.020). Most respondents with high awareness (80%) and high family support (90.9%) demonstrated good compliance. Conversely, poor taste preference was a primary barrier, with 61.1% of respondents in that category being non-compliant. Compliance with supplementary feeding among pregnant women with CED is significantly influenced by awareness, taste preference, and family support simultaneously.